Manajemen Sitasi (Psikologi, Laktasi, Gizi): Monitoring Kesehatan Fisik Jiwa Ibu Menyusui di Masa Pandemi Covid 19 - Liyanovitasari, Liyanovitasari; Oktarina, Natalia Devi (INDONESIAN JOURNAL OF COMMUNITY EMPOWERMENT (IJCE), 2022)
Transmission of Covid-19 during pregnancy or childbirth is still rare. Global guidelines released by WHO and Unicef believe that until now there is no evidence or case reports of vertical transmission from mother to fetus. In limited studies, there have been no findings of Covid-19 in breast milk in breastfeeding mothers who have been confirmed positive. These two reasons allow mothers with Covid-19 to continue breastfeeding and provide breast milk. Nowadays parents' anxiety increases with the problems of their income, food, and future. The success of breastfeeding will increase if the mother gets support from the family. This community service activity was carried out for 1 day on November 30, 2021, starting from the preparation stage, collecting data on breastfeeding mothers, providing materials, and evaluating. The material delivery stage, where breastfeeding mothers will receive "SITASI" guidelines (psychology, lactation, and nutrition) for breastfeeding mothers to improve understanding and mental and physical health during breastfeeding during the COVID-19 pandemic. At the evaluation stage, breastfeeding mothers will measure their level of understanding and the ability to carry out SITASI by using a questionnaire. The method of activity is carried out with field activities because the condition of the covid-19 pandemic has begun to decline. The media for this activity include power points and leaflets. The results of the evaluation showed that 100% of participants' knowledge increased and 75% of participants' abilities increased and all participants were very enthusiastic and had high motivation to carry out SITATION management in exclusive breastfeeding during the Covid 19 pandemic. It is hoped that this activity can increase mothers' knowledge and abilities in psychological problems, lactation and nutrition when breastfeeding babies during the COVID-19 pandemic.ABSTRAKPenularan Covid-19 selama kehamilan atau persalinan masih langka. Pedoman global yang dirilis WHO dan Unicef meyakini hingga saat ini belum ada bukti atau laporan kasus transmisi vertikal dari ibu ke janin. Dalam penelitian terbatas, belum ada temuan Covid-19 dalam ASI pada ibu menyusui yang terkonfirmasi positif. Kedua alasan tersebut memungkinkan ibu dengan Covid-19 untuk terus menyusui dan memberikan ASI. Saat ini kecemasan orang tua bertambah dengan masalah pendapatan, makanan, dan masa depan mereka. Keberhasilan menyusui akan meningkat jika ibu mendapatkan dukungan dari keluarga. Kegiatan pengabdian masyarakat ini dilakukan selama 1 hari pada 30 November 2021 yang dimulai dari tahap persiapan, pendataan ibu menyusui, pemberian materi, dan evaluasi. Tahap pemberian materi, dimana ibu menyusui akan mendapatkan pedoman â€œSITASIâ€ (psikologi, laktasi, dan gizi) pada ibu menyusui untuk meningkatkan pemahaman dan kesehatan fisik jiwa selama menyusui di masa pandemi covid 19. Pada tahap evaluasi, ibu menyusui akan diukur tinglat pemahamannya dan kemampuan menjalankan SITASI dengan menggunakan kuesioner.Metode kegiatan dilakukan dengan kegiatan lapangan karena kondisi pandemi covid-19 sudah mulai menurun. Media kegiatan ini meliputi power point dan leaflet. Hasil evaluasi menunjukkan 100% pengetahuan peserta meningkat dan 75% kemampuan peserta meningkat serta semua peserta sangat antusias dan memiliki motivasi tinggi untuk melakukan manajemen SITASI dalam pemberian ASI Eksklusif Di Masa pandemi Covid 19. Diharapkan kegiatan ini dapat meningkatkan pengetahuan dan kemampuan ibu dalam masalah psikologis, laktasi dan gizi saat memberikan ASI pada bayi selama masa pandemi Covid 19.